Cultural Defence: An Odyssey for English Courts - Madella, Irena (Kent Law Review, 2017)
When individuals commit culturally motivated acts that clash with the law, they may ask the courts to consider imperatives that influenced their criminal behaviour; namely, invoke a ‘cultural defence’ so as to lessen their responsibility. The increasing amount of literature dealing with the issue and the defence’s recognition in other jurisdictions raises the question of its incorporation in the English courts. This piece seeks to contribute to that by illustrating the difficulties of such a development. It seeks to raise the issues of reviewing the authenticity of claims and the defence’s potential misuse, and most importantly, the difficulty in understanding the ‘foreign’. While the proponents of the defence have addressed some of these issues, others remained unexamined, lacking theoretical assessment, which is essential for incorporating the fluidity and changing nature of cultures. Such examination aims to function as a warning of the enormity of the reforms suggested by the defence’s proponents.